Diagonistic Apraxia: A Unique Case of Corpus Callosal Disconnection Syndrome and Neuromyelitis Optica Spectrum Disorder - Shozawa, Hidenobu; Futamura, Akinori; Saito, Yu; Honma, Motoyasu; Kawamura, Mitsuru; Miller, Michael W.; Ono, Kenjiro (Frontiers in Neurology, 2018)
Diagonistic apraxia is a corpus callosal disconnection syndrome. Callosal lesions in Neuromyelitis optica spectrum disorder (NMOSD) have been reported, but callosal disconnection syndrome are rare. A 48-year-old woman was treated for fever and a cough before hospitalization. Her fever abated immediately, but she had balance problems in walking and standing. She also had slurred speech. On neurological examination, she had diagonistic apraxia. Her left hand moved in an uncoordinated way when she moved her right hand: changing her clothes for example or using a knife and fork. She had to instruct her left hand to stop. She had dysarthria and her gait was wide-based. She also had many callosal disconnection syndrome symptoms such as alexia of left visual field, left ear extinction, crossed optic ataxia. Using FLAIR and DWI MRI, a mixture of low and high signals, a so-called “marbled pattern,” was seen in the corpus callosum. Since the patient was positive for anti-aquaporin-4 antibody, she was diagnosed with NMOSD. After two courses of steroid pulse therapy, the symptoms improved. Here we report diagonistic apraxia and other symptoms of callosal disconnection syndrome in anti-AQP4-positive NMOSD.